Multiculture and Public Parks: Researching Super-diversity and Attachment in Public Green Space - Neal, Sarah; Bennett, Katy; Jones, Hannah; Cochrane, Allan; Mohan, Giles (Population space and place, 2015)
Situating itself in encounter and public space debates and borrowing from non‐representational theory approaches, this paper uses data from the authors' 2‐year Economic and Social Research Council research project to consider how local urban parks can work as sites of routine encounter, mixity, and place belonging. The paper explores how parks as green public spaces are important as sites of inclusive openness while the materiality of parks is a key dynamic in affective encounter processes. Parks can work as animators of social interactions, participatory practices, and place affinities across ethnic and cultural difference. The paper concludes that the concept of convivial encounter can be extended to incorporate the concept of elective practices – choosing to be in shared public space can generate connective sensibilities that are not necessarily contingent on exchange. In using parks as a lens to examine localities and diversity, the paper critically reflects on research practices for understanding and describing heterogeneous formations of multiculture and outlines how the project's research design and the fieldwork methods sought to carefully and appropriately undertake research with complexly different places and populations Copyright © 2015 John Wiley & Sons, Ltd.